KEMAMPUAN MEMBACA NYARING TEKS CERITA BUGIS SISWA KELAS V SDN 85 WANUA BARU KABUPATEN MAROS - Ayulistiana; Mayong; Yunus, Andi Fatimah (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This research is a descriptive quantitative study that aims to describe the ability to read aloud Bugis story texts of fifth grade students of SDN 85 Wanua Baru, Maros Regency. The population of this study were all fifth grade students of SDN 85 Wanua Baru, Maros Regency in the 2023/2024 school year, totaling 15 students. The withdrawal of samples in this study was carried out by means of total sampling because the population was less than one hundred. The data collection techniques used in this study were oral test techniques and recording techniques. The data obtained were analyzed using quantitative descriptive analysis. There are four aspects of assessment used in this study, namely aspects of fluency, aspects of the use of intonation, aspects of pronunciation, and aspects of voice volume. Based on the results of the data analysis obtained, it shows that the ability to read aloud Bugis story text of fifth grade students of SDN 85 Wanua Baru Maros Regency, namely (1) the fluency aspect of students who scored above 70, namely 10 people with a percentage of 60% declared unable, (2) the aspect of using intonation of students who scored above 70, namely 8 people with a percentage of 53% declared unable, (3) the aspect of pronunciation of students who scored above 70, namely 3 people with a percentage of 20% declared unable, and (4) the aspect of voice volume of students who scored above 70, namely 12 people with a percentage of 80% declared able